The palms in the traditional knowledge of indigenous Amazonian group Aguaruna-Huambisa - Roca Alcázar, Fernando (2008)
The traditional knowledge of indigenous peoples shows a different vision of the world to that of the western society. The knowledge about palms of the Aguaruna-huambisa groups living in the northwestern Peruvian forests express their palm knowledge in a particular way. Many researchers hypothesize that the Aguaruna– huambisa society, due to great botanical knowledge, are able to recognize generic taxa of palms. Scientific botanical knowledge and traditional knowledge lead to divergent perceptions of the Amazonian flora and to different ways to expressing them. The palm generic taxon, SHINKI in aguaruna language, is not recognized, but other generic taxa such as tree, vine and herb clearly appear in the traditional knowledge of this society.